Multi-criteria methodology for supporting the constructivist decision for identifying and evaluating skills for the textile printing sector - Tezza, Rafael; Zamcopé, Fábio Cristiano; Ensslin, Leonardo (Revista Gestão da Produção Operações e Sistemas, 2012)
The article analyses the study conducted in a productive sector of printed textile with the objective to createa constructivist methodology to identify, evaluate and develop the employee’s abilities and competences.A literature review treats abilities and competences in a manufacturing approach. In the case study theMethodology Multicriteria Decision Aid – Constructivist (MCDA-C) was applied and used to generateknowledge about the problem and to create the proposal. Bibliographical and documentary research aswell as half-structured interviews were used to construct the model. Through this empirical study, it waspossible to generate knowledge that was unknown before about the elements influenced by abilities andcompetences. The study identified 67 criteria that evaluate current performance and it was verified it wasbelow desired performance. This case study also describes some recommendations for running a sensitivityanalysis later.Keywords: Methodology Multicriteria Decision Aid – Constructivist (MCDA-C); Management for competency;Abilities; Textile sector.